Changing the culture: A first-hand example - Simpson, Cather (New Zealand Science Review, 2014)
In 1998, I joined the Department of Chemistry at Case Western Reserve University (CWRU) in the USA as a new Assistant Professor. Professor Mary Barkley and I, both laser spectroscopists, were hired to build a new area of strength. That we were the first women hired as academic staff in the Chemistry Department was such a remarkable event that it made the headlines in the campus newspaper (Figure 1). Today, there are six women with primary academic appointments in CWRU’s Department of Chemistry, and Barkley is the Department Chair. The fact that hiring a woman in chemistry is no longer headline material is due, in part, to a pioneering programme called ACES (Academic Careers in Engineering & Science).